Day case surgery: geographical variation, trends and readmission rates. Issue 3 (September 1989) - Henderson, J; Goldacre, M J; Griffith, M; Simmons, H M
Abstract : Data from the Oxford Record Linkage Study were analysed to determine the amount of work undertaken in day case surgery for 12 surgical conditions in five districts in the Oxford Region during the years 1976 to 1985. Record linkage was used to study readmission rates, comparing day surgery with inpatient care. The use of day surgery gradually increased in some conditions (eg, termination of pregnancy, female sterilisation) but did not increase from a fairly low base for others (eg, inguinal hernia repair, operations on varicose veins and haemorrhoids). There were striking differences between the districts in the use of day case care. For example, the use of day case care as a percentage of all hospital admissions for termination of pregnancy varied from 1% in one district to 24% in another; that for dilatation and curettage varied from 1% to 43%; and that for female sterilisation varied from less than 1% to 35%. Emergency readmission rates after day surgery were similar to those following inpatient treatment. We conclude that the use of day surgery for some conditions judged suitable for day care is still low and, even within one region, variation in the use of day surgery is considerable. The reasons for continued reluctance in some places to undertake more day surgery merit investigation.